Escape from model-land - Erica L. Thompson; Leonard A. Smith (Kiel Institute for the World Economy (IfW), 2019)
Both mathematical modelling and simulation methods in general have contributed greatly to understanding, insight and forecasting in many fields including macroeconomics. Never-theless, we must remain careful to distinguish model-land and model-land quantities from the real world. Decisions taken in the real world are more robust when informed by our best estimate of real-world quantities, than when "optimal" model-land quantities obtained from imperfect simulations are employed. The authors present a short guide to some of the temptations and pitfalls of model-land, some directions towards the exit, and two ways to escape.
Keywords: C52; C53; C6; D8; D81; 330; modelling and simulation; decision-making; model evaluation; uncertainty; structural model error; dynamical systems; radical uncertainty